DESIGN, SYNTHESIS, AND CYTOTOXICITY EVALUATION OF NOVEL OPEN-CHAIN ANALOGUES OF ANTIMYCIN A 3 AS POTENTIAL ANTI-COLORECTAL CANCER AGENTS - Arsianti, Ade; Fadilah, Fadilah; Suid, Kusmardi; Tanimoto, Hiroki; Kakiuchi, Kiyomi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Colorectal cancer is the third most common diagnosed cancer in the world. The aim of this work was to design, to synthesize, and to evaluate the novel open-chain analogues of antimycin A 3 as highly potent anti-colorectal cancer agents. Methods: Our analogue synthesis was designed by modifying the nine-membered dilactone moiety of antimycin A with a simple open-chain moiety, as well as introducing the stereocenter, and the hydroxyl groups on the side chain of the ester group. The synthesis was conducted through a sequence of reactions from Boc-L-threonine by esterification, amidation, and sharpless asymmetric dihydroxylation. After completion the synthesis, cytotoxicities of the analogues were evaluated as inhibitors of colorectal HCT-116 cells by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide cell proliferation assay. Results: Novel open-chain analogues of antimycin A were successfully synthesized in a good yield. The analogues exhibited a greater anticancer activity against colorectal HCT-116 cells than the original antimycin A 3 with 50% inhibitory concentrations ranging of 35.0-47.0 ÂµM. The results indicated that the presence of stereocenter and a hydroxylated open-chain moiety in the analogues were successfully improved its anti-colorectal cancer activity. 3 Conclusion: Our results clearly demonstrate that the opened-chain analogues of antimycin A as a promising candidates of new anti-colorectal cancer agents. Keywords: Design, Synthesis, Open-chain, Analogue, Antimycin A , Anti-colorectal cancer. 3 3